Contextualizing islamic religious education in the 21st century in Indonesia - Sya'bani, Mohammad Ahyan Yusuf (Al-Misbah (Jurnal Islamic Studies), 2024)
Education in the twenty-first century is essentially characterised by a contrast between Islamic education, which is seen in strict orthodoxy, and Western education, which tends to be secular. After this error was recognised, a concept known as the Islamization of science (a term used to describe the assimilation of Islamic principles into contemporary science) arose that attempted to reconcile Islam with knowledge. Moreover, internal issues within Islamic Religious Education itself are among the issues the organisation faces, necessitating the continuation of a structural dynamism process in order for it to endure and significantly impact the world. Islamic education faces a variety of issues in the twenty-first century, also referred to as the globalisation age. These issues include power dynamics and the direction of Islamic education, the professionalism and calibre of human resources, and curricular issues. Some people believe that practical demands, such as those of markets, fields, and employment, are the main influences on education. There is a loss of the essence of Islamic education as a basis for culture, morality, and social movement. Thus, in the twenty-first century, it is necessary to contextualise Islamic Religious Education. The findings demonstrated that the community's input, the educational process, and the educational product are the three principles that an Islamic educational institution uses to be adaptive. Several strategies, such as administrative modernization, structural differentiation, and capacity expansion, are employed in the 21st century to contextualise and dynamise Islamic Religious Education. Thus, the result of these contextualization efforts is the output of Islamic Religious Education, which also serves as an input for the community at large. This includes the production of political, economic, social, and cultural outcomes as well as changes in value systems.